OSRA Grant Cycle 2 Public Reports : Project Title: Unfamiliar Families: Syrian Refugees’ Transnational Solidarity and Kinship Networks - Sophie Richter-Devroe (17425422) (2020)
This interdisciplinary and comparative long-term ethnographic study delves into the lives of Syrian transnational refugee families in Greece and Italy, conducted by researchers spanning Qatar, Greece, Lebanon, and Italy. In the wake of the Syrian war and the ongoing migration crisis, this research explores the profound transformations experienced by Arab families, a cornerstone of the region's social and political landscape. The study sheds light on the critical role of family and kin as vital support networks for migrants, often surpassing formal institutional channels. It emphasizes the need for a deeper understanding of the various dimensions of the Arab family, particularly in the context of asylum and family reunification policies. Additionally, the research reveals how migration and displacement reshape families, leading to separations and the formation of new familial bonds through marriage and solidarity activism. These findings have been shared in academic, activist, development, and policy forums across multiple countries, sparking essential discussions on the role of families in the transnational realm of forced migration and displacement.